Assessment of the management of student affairs records: Case of the University of Mpumalanga in South Africa. (7th October 2019) - Netshakhuma, Nkholedzeni Sidney
Abstract : Purpose: The purpose of this paper is to assess records management components, such as record scheduled, records appraisal, destroyed/disposed, retained, training of staff on the management of the student affairs records (SARs), provided access, the challenges associated with efficient management of SARs and strategies for effective management of SARs, to determine the extent the Student Affairs Department (SAD) complies with the University of Mpumalanga (UMP) records management policy. Design/methodology/approach: This paper uses qualitative methodology of a triangulation of data collection and this included interviews, document analysis and observation. Findings: The literature review, as well as the interview, revealed that findings on the UMP records management policy are multi-layered. A number of participants mentioned lack of records centre, records retention and appraisal of records, records management training and managing access to information as a challenge to the management of SARs. Research limitations/implications: The research was only limited to the UMP, Student Affairs Division, with a population of 15 staff members even though the findings can be applied to all the universities in South Africa. Practical implications: SAD has a unique contribution to make to ensure that records created within their division are managed in terms of the UMP records management policy by ensuring that components such as records storage retention and appraisal of records management training and managing access to information are adhered to. Social implications: Failure to comply with the UMP records management policy by the Student Affairs Division will contribute to the loss of institutional memories, non-compliance with legislations such as Promotion of Access to Information Act 2000, National Archives and Records Services Act 46 of 1996 and the Protection of Personal Information Act No 4. Of 2013. Originality/value: The research appears to be the first of its kind, to the best of the authors' knowledge, to assess SARs at the UMP, South Africa.